Manajemen Sumber Daya Manusia yang "Fit": Keunggulan Kompetitif Organisasi - Bertha Silvia Sutejo (Jurnal Manajemen Maranatha, 2004)
Importance manages human resource management in business agenda now. Human resource management (HRM) are asset which must managed so can be fit with business needed and can help organization to be more competitive. Therefore, HRM considered not just as strategic factor with role importance in implementation strategy but also calculation as resource can achieve competitive advantage. Exist assume that close link between business strategy and HRM methods based of contingency theory. Contingency theory holds that human resource management methods are selected in accordance with the type of competitive strategy adopted by a business. It is moreover assumes that companies that closely coordinate their business strategy and HRM activities achieve better performance than companies that do not. Differences of business and combination HRM have different effect on performance organization. However, that differences not always consistent with contingency theory. Therefore, needed match between business strategy and HRM practices so that produce organization performance can achieve competitive advantage.Keyword: business strategy, human resource management, firm performance, competitive advantage